EVALUATION THE PROPERTIES OF PURIFIED LACCASE EXTRACTED FROM SOME LOCAL PLANTS UNDER THE OPTIMUM CONDITIONS - Younis Swadi Tlaiaa; Sahar I.H; Mohanad J. M-Ridha (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study set out to screen 36 common plants which have the greatest level of laccase enzyme activity. It revealed that the enzymatic activity of fenugreek seeds was the highest in comparison with other plants. The optimal enzyme-specific activity was 5340.38 units per milligram protein which were obtained by extracting the enzyme with a sodium phosphate buffer at a concentration of 0.02 M and pH 8.0, at a ratio of 1:40 (weight to volume), and extracting time of 210 minutes. The enzyme yield was 27.6% after extraction and purification by gel filtration using Sephacryl S-3 after 1.01 purification fold. The optimum circumstances for enzymatic activity and stability were found by using 0.1 M sodium acetate as a buffer at pH 5. Also, the maximal activity and stability of purified laccase was obtained at 20 oC for 15 min by using o-tolidine as a substrate. This research sheds light on how to isolate and characterize the laccase enzyme, an important biochemical with numerous biotechnological and technological uses through fenugreek seeds as a source of the laccase.